Neziskové organizace jako významní aktéři v oblasti sociálních služeb - Varvažovská, Pavla (Univerzita Pardubice, 2008)
Non-government non-profit organizations are significant actors in the sphere of social services nowadays. From this reason the author of the thesis attempted to evaluate current role of these organizations especially in relation to the new code 108/2006 Sb. concerning social services, to highlight the importance and necessity of these organizations and evaluate development of their role in the future.
Keywords: non-government non-profit organization; social services; standards of social services; community planning